Cooperation after divorce : An RCT study of the effects of a digital intervention platform on self-perceived stress - Ciprica, Ana, (Colegio Oficial de Psicólogos de Madrid, 2020)
Divorce has long been considered one of the most pervading stressful life events and has consistently been associa- ted with high stress levels and subsequent poorer mental- and physical health. This study evaluates the effectiveness of the Cooperation after Divorce (CAD) online intervention on perceived stress immediately following divorce. The studys design was a one-year longitudinal randomized controlled trial including an intervention group (n = 1,031) and a no-treatment control group (n = 825) with four assessments of perceived stress levels (at baseline and 3, 6 and 12-mon- ths post-divorce). The CAD intervention consists of a 17-module online platform designed to support divorcees and their children post-divorce. Data analyses consisted of linear mixed effect modeling and means comparisons. The study found that the intervention significantly accelerated the reduction of perceived stress among recently divorced adults when compared with controls. Further, after one year, stress levels in the intervention group were reduced to normed national stress levels while the mean stress level in the control group remained substantially higher. The results suggest that on- line interventions may offer long-term public health benefits in reducing stress among newly divorced individuals and speak to potential implications related to the services provided for people undergoing divorce.